1996
DOI: 10.1523/jneurosci.16-16-05106.1996
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Axons Recognize Specific Guidance Cues Present in the Deafferented Adult Rat Superior Colliculus

Abstract: During development, retinal ganglion cell axons establish a topographically ordered projection from the retina to the superior colliculus (SC). The putative guidance activities for retinal axons that operate during embryonic development are not detectable in the normal adult SC. However, these cues reappear upon transection of the optic nerve of adult rats. In the present study, we used a modified version of the "stripe assay," in which membranes from either anterior or posterior SC alternated with laminin str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Fiber tract lesion of the retinocollicular projection in the rat is an established model to investigate secondary neuronal loss in degenerative processes of the mammalian CNS because of its good surgical accessibility and well known kinetics of cell death (Villegas-Perez et al, 1988;Mey and Thanos, 1993;Bähr and Bonhoeffer, 1994;Bähr and Wizenmann, 1996;Klöcker et al, 1997Klöcker et al, , 1998Kermer et al, 1999aKermer et al, , 2000. Transection of the ON induces a delayed death of 80 -90% of RGCs within 14 d, starting around day 4 and reaching a maximum on day 7 after axotomy (Eschweiler and Bähr, 1993;Mansour-Robaey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Fiber tract lesion of the retinocollicular projection in the rat is an established model to investigate secondary neuronal loss in degenerative processes of the mammalian CNS because of its good surgical accessibility and well known kinetics of cell death (Villegas-Perez et al, 1988;Mey and Thanos, 1993;Bähr and Bonhoeffer, 1994;Bähr and Wizenmann, 1996;Klöcker et al, 1997Klöcker et al, , 1998Kermer et al, 1999aKermer et al, , 2000. Transection of the ON induces a delayed death of 80 -90% of RGCs within 14 d, starting around day 4 and reaching a maximum on day 7 after axotomy (Eschweiler and Bähr, 1993;Mansour-Robaey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Knoll et al (2001a) demonstrated a graded expression pattern of ephrinA in the SC of mice before and after lesion of the optic nerve, remarkably similar to the expression patterns found during development, suggesting that topographic guidance information for a successful re-establishment of the retinocollicular projection was available. Interestingly, RGC axons do not exert guidance preferences in response to membranes from adult unlesioned SC, but only in response to membranes from deafferented SC (Wizenmann et al 1993;Bahr and Wizenmann 1996). In normal adult tissue, the repellent activity of ephrinA is blocked by coexpression of EphA receptors in the SC, such that EphA receptors on retinal axons cannot bind the ephrins in the SC membranes.…”
Section: Neuroregenerationmentioning
confidence: 99%
“…In the developing CNS specific factors are expressed at the midline that attract or repulse fibers in order to establish the correct pattern. Whether these guidance cues are still expressed in the mature CNS or whether their reexpression is only triggered by a lesion is not yet clear (e.g., in the visual system lesions induce guidance cues; Wizenmann et al, 1993;Bä hr et al, 1996).…”
Section: Topographic Sprouting Of Corticopontine Fibersmentioning
confidence: 99%